Oedipus and the Paternal Metaphor - Žerjav, Ana (Filozofski vestnik, 2011)
The article shows the importance of the paternal metaphor and the function of the father in psychoanalysis, as well as some misunderstandings that can occur regarding this function in philosophy, namely Deleuze and Guattari's critique of the father as a normative function of castration. It focuses on Freud's and Lacan's conception of the Oedipus complex and underlines some crucial changes that Lacan introduced while reading Freud's work and while constantly returning in his teaching to his own previous conceptions. Finally, the article argues that it is not possible to ignore the function of the father and aspire to create a new sort of psychoanalytic practice by entirely avoiding the difficult and constitutive role of this function.